HISTORIA DE LA ERMITA DE NUESTRO SEÑOR DE LA AGONÍA. LIBERIA GUANACASTE - Solano Muñoz, Edgar (2011)
The article discusses the history of the Shrine of Our Lord of the Agony, located in Liberia, Guanacaste. Communal efforts of the government of Costa Rica to begin construction of the Hermitage emerged in the decade of the 40s of the nineteenth century, but due to the war in Central America, was restored to the sixties of the century, when they finally launched